Days of futures past : integrating physiology, microenvironments, and biogeographic history to predict response of frogs in neotropical dry-forest to global warming (2017)
Global climate is changing at an accelerated rate with a predicted increase in temperature of up to 5°C by 2070. Species present in biomes already exposed to high temperatures could be near their thermal limit, and further temperature increase could threaten their survival. Organisms directly experience micro-environments rather than regional temperatures, however. Thus, predicting the response of species to climate change requires understanding how variation in regional temperatures relates to variation in the micro-environment, as well as understanding a species' physiological tolerance to thermal extremes. Finally, understanding how readily a species' thermal niche could evolve to new conditions, is informed by inferring the historical labiality of this trait in a comparative phylogenetic context. We applied this integrative approach to the study of two sympatric frog species (Anura: Leptodactylidae: Leiuperinae) from the xeric lowlands of the Caribbean Coast of South America: the Colombian four-eyed frog, Pleurodema brachyops, and the túngara frog...